Rapid creation system of morphologically and functionally communicative three‐dimensional cell‐dense tissue by centrifugation. (2nd October 2018) - Haraguchi, Yuji; Matsuura, Katsuhisa; Kagawa, Yuki; Hasegawa, Akiyuki; Kubo, Hirotsugu; Shimizu, Tatsuya
Abstract : This study reports a rapid fabrication system of a morphologically and functionally communicative three‐dimensional (3D) cell‐dense tissue without scaffolds by centrifugation. The tight adhesion between C2C12 myoblasts and culture surface was accelerated without significant cell damage by centrifugation (80 x g, 37 °C, 30 min). A thicker tissue created on a temperature‐responsive culture surface was harvested by decreasing temperature. The 3D myoblast tissues having approximately 200 μm‐thickness were created at 1.5 h [centrifugation (80 x g, 37 °C) for 30 min and tissue harvest for 1 h]. However, in the case of without centrifugation, the myoblast tissues had fragile parts even at 7.5 h after the incubation. Additionally, electrically/functionally communicative and thicker human induced pluripotent stem (iPS) cell‐derived cardiac tissues were created rapidly by the centrifugation and cultivation at 37 °C. We report a centrifugation system that significantly shortens the creation time of 3D tissues. We envision that this procedure will contribute to the field of tissue engineering and regenerative medicine. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 34:1447–1453, 2018